MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM SENI MUSIK MELALUI PENDEKATAN KONTEKSTUAL PADA MATERI RAGAM LAGU DAERAH NUSANTARA (Penelitian Tindakan Kelas pada Siswa Kelas V-B SDN Tegalkalong Kecamatan Sumedang Utara Kabupaten Sumedang) - Nugraha, Anggi Anggriyana (2017)
Based on the early results data of research found a problems the low result value of student's study in culture art lesson and the archipelago song of variety material skill. In other than one of student's lesson is value in knowledge aspect. Effort has to do for value all of aspect and critical thinking ability increasing in art music is contextual approach. The reason for choosing a contextual approach is because the learning step is in line with the learning objectives that want to achieve constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. This research is one of the class action research with Kemmis and Mc. Taggart's model. The research with three cycles do at Tegalkalong Elementary School's the fifth-B class of North Sumedang Subdistrict, Sumedang Regency. The research purpose is able to know of teacher performance in the planning and in the implementation, student's activity, and studying results increasing of critical thinking ability in music art. The first cycle result of teacher performance in the achievable planning 75%, achievable implementation 71,79%, achievable student 69,44%, and critical thinking ability completeness 37,5%. Teacher performance in the planning has increased in the second cycle's 91,66% and becoming 100% in the third cycle. Teacher performance in the implementation has increased in the second cycle's 89,74% and becoming 100% in the third cycle. Student's activity has increased in the second cycle 78% and becoming 89,81% in the third cycle. Critical thinking ability in music art increased from 66,7% in the second cycle's and becoming 87,5% in the third cycle. The research results is inferential that using of contextual approach is able to be increasing critical thinking ability (knowledge, understanding, skills, attitude, appreciation, and habits) of music art at Tegalkalong Elementary School's the fifth-B class of North Sumedang Subdistrict, Sumedang Regency. Keyword: the critical thinking ability in the music art, contextual approach, the archipelago song